(3CSeGA GdQLGds - (3eMeO Hf GdMSf Hf Ydj GdWhSj , CHh LYaQ,J (B460 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Mb MeOg hGdUdGI hGdSdGe Ydi NjQ Ndbg eMeO hBdg GdWGgQjf s
(3BNQgG (B:s
(3Je GdcJGH hddg GdMeO s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B84 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B202s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs